The Neon Gap: Probing Ionization with Dwarf Galaxies at z ∼ 1 - John Pharo; Yicheng Guo; David C. Koo; John C. Forbes; Puragra Guhathakurta (The Astrophysical Journal Letters, 2023)
We present measurements of [Ne iii ] λ 3869 emission in z ∼ 1 low-mass galaxies taken from the Keck/DEIMOS spectroscopic surveys HALO7D and DEEPwinds. We identify 167 individual galaxies with significant [Ne iii ] emission lines, including 112 “dwarf” galaxies with $log(M_{\star }/M_{\odot })\lt \,9.5$ , with 0.3 < z < 1.4. We also measure [Ne iii ] emission from composite spectra derived from all [O ii ] λλ 3727,3729 line emitters in this range. This provides a unique sample of [Ne iii ] emitters between well-studied emitters at z = 0 and 2 < z < 3. To study evolution in ionization conditions in the interstellar medium (ISM) over this time, we analyze the log([Ne iii ] λ 3869/[O ii ] λλ 3727,3729) ratio (Ne3O2) as a function of the stellar mass and of the log([O iii ] λλ 4959,5007/[O ii ] λλ 3727,3729) ratio (O32). We find that the typical star-forming dwarf galaxy at this redshift, as measured from the composite spectra, shares the Ne3O2– M _⋆ relation with local galaxies but has higher O32 at a given Ne3O2. This finding implies that the ionization and metallicity characteristics of the z ∼ 1 dwarf population do not evolve substantially from z ∼ 1 to z = 0, suggesting that the known evolution in those parameters from z ∼ 2 has largely taken place by z ∼ 1. Individual [Ne iii ]-detected galaxies have emission characteristics situated between local and z ∼ 2 galaxies, with elevated Ne3O2 and O32 emission potentially explained by variations in stellar and nebular metallicity. We also compare our dwarf sample to similarly low-mass z > 7 galaxies identified in JWST Early Release Observations, finding four HALO7D dwarfs with similar size, metallicity, and star formation properties.